(untitled) (Journal of Informatics Education and Research, 2024)
Purpose: The research articles explore the dimension of SMEs (Small and Medium enterprises) in terms of characteristics, opportunities, challenges, service criteria, technology adoption, and Support systems for growth and development. The research article provided in-depth insight into how the Industry, Government, and policymakers can benefit from the data insights. Methodology/Design/Approach: These ventures suffer operational and structural issues due to the lack of infrastructure for implementing financial technologies. To address this issue, the classification Approach has been applied, and various aspects of SMEs have been addressed analytically. Results: The results show that with technology, SMEs can get more funds regarding their business process, and technology will enhance the supply chain architecture. Originality: This Literature review paper focuses on the different dimensions of Fintech implementation in SMEs in global trade. A significant gap is seen between developed and developing countries concerning technological advancement in business activities.